Cyclostationarity: Theory and Methods III Contributions to the 9th Workshop on Cyclostationary Systems and Their Applications, Grodek, Poland, 2016 - Chaari, Fakher; Leskow, Jacek; Napolitano, Antonio; Zimroz, Radoslaw; Wylomanska, Agnieszka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book gathers contributions presented at the 9th Workshop on Cyclostationary Systems and Their Applications, held in Gródek nad Dunajcem, Poland in February 2016. It includes both theory-oriented and practice-oriented chapters. The former focus on heavy-tailed time series and processes, PAR models, rational spectra for PARMA processes, covariance invariant analysis, change point problems, and subsampling for time series, as well as the fraction-of-time approach, GARMA models and weak dependence. In turn, the latter report on case studies of various mechanical systems, and on stochastic and statistical methods, especially in the context of damage detection. The book provides students, researchers and professionals with a timely guide to cyclostationary systems, nonstationary processes and relevant engineering applications.
From the content: Weak Dependence: An Introduction Through Asymmetric ARCH Models -- Subsampling for Non‐Stationary Time Series With Long Memory and Heavy Tails Using Weak Dependence Condition -- Change‐Point Problem in the Fraction of Time Approach.
Keywords: Machinery; Multibody systems; Vibration; Mechanics, Applied; Signal processing; Mathematical models; Security systems; Machinery and Machine Elements; Multibody Systems and Mechanical Vibrations; Signal, Speech and Image Processing; Mathematical Modeling and Industrial Mathematics; Security Science and Technology